The Relationship of Attitudes toward Other Religious Groups with Perceived Islamophobia, Intergroup Contact, and Social Identity: A Study among Muslims Living in Western Countries - Kenan Sevinç; Metin Güven (Rize İlahiyat Dergisi)

(untitled)
The Muslim population in Western countries gradually increases, and thereby, individual, social, cultural, economic, political, etc. matters related to the lives of Muslims draw researchers’ attention day by day. Muslims, who make efforts to survive within the given population as a minority group, may encounter negative attitudes and behaviors in different life venues such as exclusion, discrimination, prejudice, labeling or stigmatization, hatred, anger, and violence. In this regard, the literature addressed verbal taunting, obstructing religious practices, workplace discrimination, travel discrimination, armed attacks, threats, bullying, and vandalism as significant problem instances. Particularly, the 9/11 attacks had caused a breakthrough change in the lives of the Muslim population in terms of the addressed negative attitudes and behaviors, causing such complicated and deleterious incidents to happen increasingly. Therefore, the relationships of different religious groups with each other living in Western society prompted a significant scholarly interest. The existing literature explored the thoughts, attitudes, and behaviors of religious groups toward each other and found that Muslims have to struggle with detrimental attitudes more compared to any other religious group. In this regard, an important question that comes to mind is what thoughts, feelings, and attitudes Muslims living in Western countries may have toward other religious groups while facing negative and complicated thoughts, attitudes, and actions of other religious groups. Accordingly, this research explored the attitudes of Muslims living in Western countries toward other religious groups and the relationship of these attitudes with intergroup contact, quality of contact, perceived Islamophobia level, and social identification level. As a quantitative study, we collected the data with the survey technique and ran the correlational analysis. The cross-sectional data came from 158 participants (93 Males (58.9%) - 65 Females (41.1%)), who mostly live in the U.S., the U.K., Germany, and other Western countries, aged 18 and 55+. The survey deployed “Social Identification Scale” and “Perceived Islamophobia Scale.” In addition, we ask questions to the participants regarding (a) the frequency and quality of intergroup relations and (b) the attitudes towards other religious groups. Results indicated that (a) Catholics are the most positively regarded religious group for Muslims and they are the group with whom Muslims have the highest frequency of contact; (b) attitudes toward other religious groups were associated with frequency of contact and positive evaluation of contact; (c) there was no statistical relationship between levels of social identification, contact and perceived Islamophobia and attitudes towards other religious groups, and (d) among religious groups, perceived Islamophobia was only associated with attitudes toward Jews and evaluations of contact with this group. We discuss the study implications, limitations as well as future research avenues.